VD_FINDINFO Jug / 2024 / 358 vom 25. November 2022 - VD Tribunal cantonal (2022)
FRAIS JUDICIAIRES, DÉPENS, COMPENSATION DE CRÉANCES, TRIBUNAL FÉDÉRAL, DÉCISION DE RENVOI | 423 al. 1 CPP (CH), 426 al. 1 CPP (CH), 429 al. 1 let. a CPP (CH), 442 al. 4 CPP (CH)